2015
DOI: 10.1080/15389588.2014.995266
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Model Prediction of Pulmonary Contusion in Vehicle-to-Vehicle Simulations of Real-World Crashes

Abstract: A preliminary threshold for maximum crush was calculated to predict a clinically significant volume of pulmonary contusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Andersson et al performed an analysis on child size and reported that light vehicles required higher performance interior restraint systems than larger vehicles [ 22 ]. Danelson et al and Digges et al analyzed lung contusions during motor vehicle accidents [ 23 , 24 ]. Klein et al reported that body shape altered impact to the femur [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Andersson et al performed an analysis on child size and reported that light vehicles required higher performance interior restraint systems than larger vehicles [ 22 ]. Danelson et al and Digges et al analyzed lung contusions during motor vehicle accidents [ 23 , 24 ]. Klein et al reported that body shape altered impact to the femur [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the method has become of increasing interest due to potential diagnostic and therapeutic utility also in other medical fields, with some adaptations to fluid mechanics. The method has been studied, inter alia, for the prediction of an extent of post-traumatic lung injuries, which includes the evaluation of the accompanying lung inflammatory components (Danelson and Stitzel 2015;Lorkowski et al 2015). Other novel applications of FEM extend to the evaluation of the biomechanical properties of the eustachian tube that connects the middle ear to the nasopharynx, which has to do with cartilage stiffness and mucosal adhesion in otitis media (Malik et al 2016).…”
Section: Discussionmentioning
confidence: 99%